Knowledge of Malaria Management in Pediatrics among Undergraduate Pharmacy Students in University of Ibadan, Nigeria (African Journal of Biomedical Research, 2023)
Malaria is a foremost preventable cause of death and a major public health concern. Inadequate knowledge of malaria management in pediatrics among future pharmacists could affect the standard of services rendered. Pharmacists are the most accessible healthcare professional; thus they should possess good knowledge of malaria management in pediatrics. This study was designed to assess pharmacy students’ knowledge of malaria management in pediatrics. A cross-sectional survey among 140 pharmacy students of a Nigerian University, between July and August 2019, using a validated self-administered questionnaire. Data were summarized with descriptive statistics. Association between knowledge and year of study was determined using Chi-square, with p